Synthesis and degradation of FtsZ quantitatively predict the first cell division in starved bacteria. Issue 11 (5th November 2018) - Sekar, Karthik; Rusconi, Roberto; Sauls, John T; Fuhrer, Tobias; Noor, Elad; Nguyen, Jen; Fernandez, Vicente I; Buffing, Marieke F; Berney, Michael; Jun, Suckjoon; Stocker, Roman; Sauer, Uwe
Abstract: In natural environments, microbes are typically non‐dividing and gauge when nutrients permit division. Current models are phenomenological and specific to nutrient‐rich, exponentially growing cells, thus cannot predict the first division under limiting nutrient availability. To assess this regime, we supplied starving Escherichia coli with glucose pulses at increasing frequencies. Real‐time metabolomics and microfluidic single‐cell microscopy revealed unexpected, rapid protein, and nucleic acid synthesis already from minuscule glucose pulses in non‐dividing cells. Additionally, the lag time to first division shortened as pulsing frequency increased. We pinpointed division timing and dependence on nutrient frequency to the changing abundance of the division protein FtsZ. A dynamic, mechanistic model quantitatively relates lag time to FtsZ synthesis from nutrient pulses and FtsZ protease‐dependent degradation. Lag time changed in model‐congruent manners, when we experimentally modulated the synthesis or degradation of FtsZ. Thus, limiting abundance of FtsZ can quantitatively predict timing of the first cell division. Synopsis: Real‐time metabolomics and single‐cell microscopy reveal that non‐dividing bacteria rapidly synthesize biomass from sporadic glucose. First division occurred when protein FtsZ reached critical abundance. Metabolism and division occurrence was studied in starved Escherichia coli under pulsed glucose. Real‐time metabolomics revealed that non‐dividing bacteria rapidly synthesized biomass from pulsed glucose. Lag time to division depends on the frequency of the glucose pulses. First division occurrence is quantitatively predicted from changing FtsZ abundance, subject to pulse‐formed synthesis and ClpXP protease‐based degradation. Abstract : Real‐time metabolomics and single‐cell microscopy reveal that non‐dividing bacteria rapidly synthesize biomass from sporadic glucose. First division occurred when protein FtsZ reached critical abundance.